Ethics and the use of competitive information acquisition strategies - Beltramini, Richard F. (Journal of business ethics, 1986)
Several business trends have forced accelerated efforts to acquire competitive intelligence. While coverage of business ethics in classroom instruction has accelerated, concerns over unethical competitive information acquisition strategies persist. The frequency of use by individuals, their companies, and their competitors is assessed, and the findings reveal the extent of this ethics gap.